The Role of Mobile Technologies in Tracking Cyberbullying Trends and Social Adaptation among Teenagers - Vichayanan Rattanawiboonsom; Sikandar, Huma; Uthen Thatsaringkharnsakun; Nohman Khan (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This study aimed to investigate the role of mobile technologies in tracking cyberbullying trends and promoting social adaptation among teenagers through a comprehensive bibliometric analysis. The study sought to identify key trends, influential factors, and potential intervention strategies in this rapidly evolving field. A systematic review following PRISMA guidelines was conducted, analyzing 64 documents from the Scopus database published between 2014 and 2024. The methodology employed bibliometric analysis techniques, including co-occurrence networks, bibliographic coupling, and keyword analysis. The results revealed a significant increase in research on cyberbullying and mobile technologies over the past decade. The analysis identified several prominent clusters, including the prevalence of cyberbullying, the role of social media platforms, and the effectiveness of intervention strategies. Gender and age emerged as influential factors in cyberbullying experiences and behaviors. The accessibility and ubiquity of mobile devices were found to play a crucial role in cyberbullying trends. The findings emphasize the importance of developing evidence-based approaches that leverage mobile technologies for intervention. Comprehensive educational programs and innovative approaches, such as chatbot-based coaching interventions, showed promise in reducing cyberbullying and promoting positive social adaptation. The study underscores the complex and multifaceted nature of cyberbullying, necessitating an interdisciplinary approach integrating insights from psychology, sociology, and computer science. The development of specialized assessment tools and the use of machine learning algorithms for detecting cyberbullying incidents highlight the increasing sophistication of research methodologies in this field. Future research should focus on longitudinal studies and the development of innovative, evidence-based intervention strategies.